Our Environment: A Glimpse at What Mainers Value - Anderson, Mark; Noblet, Caroline; Teisl, Mario (Maine Policy Review, 2012)
Understanding environmental worldviews is important because values can play a strong part in defining and resolving policy debates. Mark Anderson, Caroline Noblet and Mario Teisl present analysis of a survey that included questions about Mainers’ environmental values. They note that people can value the environment in multiple ways at the same time, and that these values are not necessarily mutually exclusive. In the end, they say, “values matter” in environmental policy.
Keywords: Maine; environmental values; policy